The Evaluation of Thyroid Diseases in Patients with Pemphigus Vulgaris - Mukaddes Kavala; Esra Kural; Emek Kocaturk; Ilkin Zindanci; Zafer Turkoglu; Burce Can (The Scientific World Journal)
Background. Thyroid disorders may affect all of the organ systems of the body and they are also highly associated with a wide variety of skin disorders. The aim of this study was to investigate the prevalence of thyroid function abnormalities and thyroid autoimmunity in patients with pemphigus vulgaris (PV) and to determine the association between thyroid disorders and clinical involvement and systemic corticosteroid treatment in patients with PV. Methods. The study consisted of eighty patients with PV and eighty healthy individuals. Thyroid functions (fT3, fT4, and TSH) and thyroid autoimmunity (anti-thyroid peroxidase (anti-TPO), and anti-thyroglobulin (anti-Tg) antibodies) were investigated in both groups. Primary thyroid disease (PTD) was diagnosed with one or more of the following diagnostic criteria: (i) positive antithyroid antibodies, (ii) primary thyroid function abnormalities. Results. Significant changes in the serum thyroid profile were found in 16% (13/80) of the PV group and 5% (4/80) of the control group. Positive titers of antithyroid antibodies (anti-TPO and anti-Tg) were observed in 7 patients (9%) with PV and one in the control group (1,2%). Hashimoto thyroiditis was diagnosed in 9% of PV patients and it was found to be more prevalent in the mucosal form of PV. PTD was found in 13 of (%16) PV patients which was significantly high compared to controls. PTD was not found to be associated with systemic corticosteroid use. Free T3 levels were significantly lower in PV group compared to the control group and free T4 levels were significantly higher in PV group compared to the controls. Conclusions. PV may exist together with autoimmune thyroid diseases especially Hashimoto thyroiditis and primer thyroid diseases. Laboratory work-up for thyroid function tests and thyroid autoantibodies should be performed to determine underlying thyroid diseases in patients with PV.